Integrated stratigraphy of the Kimmeridge Clay Formation (Upper Jurassic) based on exposures and boreholes in south Dorset, UK - Morgans-Bell, H; Coe, A; Hesselbo, S; Jenkyns, H; Weedon, G; Marshall, J; Tyson, R; Williams, C (Cambridge University Press, 2001)
For the purposes of a high-resolution multi-disciplinary study of the Upper Jurassic Kimmeridge Clay Formation, two boreholes were drilled at Stanworth Quarry and one at Metherhills, south Dorset, UK. Together, the cores represent the first complete section through the entire formation close to the type section. We present graphic logs that record the stratigraphy of the cores, and outline the complementary geophysical and analytical data sets (gamma ray, magnetic susceptibility, total organic carbon, carbonate, δ13Corg). Of particular note are the new borehole data from the lowermost part of the formation which does not crop out in the type area. Detailed logs are available for download from the Kimmeridge Drilling Project web-site at http://kimmeridge.earth.ox.ac.uk/. Of further interest is a mid-eudoxus Zone positive shift in the δ13Corg record, a feature that is also registered in Tethyan carbonate successions, suggesting that it is a regional event and may therefore be useful for correlation. The lithostratigraphy of the cores has been precisely correlated with the nearby cliff section, which has also been examined and re-described. Magnetic-susceptibility and spectral gamma-ray measurements were made at a regular spacing through the succession, and facilitate core-to-exposure correlation. The strata of the exposure and core have been subdivided into four main mudrock lithological types: (a) medium-dark-dark-grey marl; (b) medium-dark-dark grey-greenish black shale; (c) dark-grey-olive-black laminated shale; (d) greyish-black-brownish-black mudstone. The sections also contain subordinate amounts of siltstone, limestone and dolostone. Comparison of the type section with the cores reveals slight lithological variation and notable thickness differences between the coeval strata. The proximity of the boreholes and different parts of the type section to the Purbeck-Isle of Wight Disturbance is proposed as a likely control on the thickness changes.